STRUCTURAL AND MORPHOLOGICAL STUDY OF BIMETALLIC PHOSPHIDE Ni-Cu-P (Scientific journal of the Fergana State University, 2025)
Renewable hydrogen fuels are currently receiving more interest from scientists worldwide.  The article examined the physico-chemical (electronic structure and conductivity, structural morphology) and onestep hydrothermal synthesis method of double metal phosphide with NixCuyPz composition.